Study of Two Isoforms of Lipoxygenase by Kinetic Assays, Docking and Molecular Dynamics of a Specialised Metabolite Isolated from the Aerial Portion of Lithrea Caustica (Anacardiaceae) and Its Synthetic Analogs - Urzua-Moll, A; Mascayano-Collado, C; Muñoz-Ramirez, A; Torrent-Farias, C (Elsevier Ltd, 2020)
Our investigation focused on the characterization and study of epicuticular leaf extracts (dichloromethane extract) and certain derivatives of Lithrea caustica (Molina) Hook and Arn. (Anacardiaceae) as inhibitors of 15 soybean and 5 human lipoxygenases (15-sLOX and 5-hLOX). From the epicuticular extract of leaves, the compound (Z)-3-(pentadec-10′-enyl)-catechol (Litreol) was isolated, and three hemisynthetic derivatives were prepared, as they are 3-pentadecylcatechol, (Z)-1,2-diacetyl-3-(pentadec-10′-enyl)-benzene and 1,2-diacetyl-3-pentadecylbenzene. The inhibitory activities for the four compounds against 15-sLOX and 5-hLOX were determined, being (Z)-3-(pentadec-10′-enyl)-catechol (IC50 54.77 μM and 2.09 μM, respectively) and 3-pentadecylcatechol (IC50 55.28 μM and 2.74 μM, respectively), the most interesting compounds assayed. The kinetic studies for (Z)-3-(pentadec-10′-enyl)-catechol and 3-pentadecylcatechol showed a mixed inhibition mechanism to 5-LOX. Finally, docking and molecular dynamics studies were performed to characterize and describe how the chemical structures could be correlated to the decreased 5-hLOX activity observed in the in vitro studies. © 2020 Elsevier Ltd
Keywords: Lithrea caustica; Anacardiaceae; Natural products; 5-LOX inhibition; Anticancer agents; Molecular dynamics